16.8k views
2 votes
Which is equivalent to the expression? x2 + 6x + 4 A) (x + 3)2 + 5 B) (x + 3)2 − 5 C) (x − 3)2 + 5 D) (x − 3)2 − 5

User IraSenthil
by
5.4k points

2 Answers

5 votes

Answer:

Explanation:

(x + 3)² − 5 because :

(x + 3)² − 5 = x² +6x+9 -5 =x²+6x+4

User Raulmarcosl
by
5.7k points
3 votes

Answer:

B)
(x + 3)^2 - 5

Explanation:

the equation is:
x^2 + 6x + 4

we have an equation of the form


ax^2+bx+c

where


a=1,b=6,c=4

and we must complete the square to obtain a perfect square binomial,

we must add and substract the following:


((b)/(2a) )^2

which is:


((6)/(2*1) )^2=3^2

and then the equation becomes:


x^2 + 6x + 4+3^2-3^2

where the terms
x^2+6x+3^2 are the components of the perfect square binomial:
(x+3)^2

and thus, the equation now is:


(x+3)^2+4-3^2\\=(x-3)^2+4-9\\=(x+3)^2-5

the answer is: B)
(x + 3)^2 - 5

User Jeffreyveon
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.